A mobility framework to improve heterogeneous wireless network services. (3rd January 2011) - Shen, Chong; Du, Wencai; Atkinson, Robert; Irvine, James; , Dirk Pesch
We propose and investigate the Internet Protocol version 6 (IPv6) enabled mobility framework to improve the user mobility experience in heterogenous wireless networks. The framework considers the traditional IP network infrastructure, IPv6 based mobility support, multihoming, traffic flow transparent handovers and flat/dynamic mobility policy enforcement to guarantee the Quality of Service (QoS) and Quality of Experience (QoE) with ubiquitous connectivity. Using Network Mobility (NEMO) we can provide a flexible network integration mechanism across WiFi, WiMax and UMTS systems vertically. The flexible approach overcomes the limitation of different networks access denial when nodes move using two operations: Policy enforced handover management and Dynamic handover implementation. The paper describes the design rationale behind the solution, introduces an experimental testbed and simulation models, validates mobility related services performance, and discusses our research findings.